1994
DOI: 10.1159/000227306
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucinous Adenocarcinomas and Signet-Ring Cell Carcinomas of Colon and Rectum

Abstract: Of 352 patients with colorectal carcinoma followed for a minimum of 5 years after surgery, 39 cases (11.1%; median age 60 years) had mucinous adenocarcinoma, and 4 (1.1%; median age 62 years) had signet-ring cell carcinoma. Mucinous carcinomas were most frequently located in the rectum (61.5%) and in the sigmoid colon (15.3%) and presented with stage C and D disease in 41 and 15% of the cases, respectively. Disease recurrence was more frequently observed in patients with mucinous (51.7%) or signet-ring lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
83
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 6 publications
(21 reference statements)
11
83
0
6
Order By: Relevance
“…The reported 5-year survival in the literature is 9-37%, [1][2][3][4][5][6][7][8][9][10] which is comparable to the 33% survival in this study. The literature contains limited data on the molecular features of signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The reported 5-year survival in the literature is 9-37%, [1][2][3][4][5][6][7][8][9][10] which is comparable to the 33% survival in this study. The literature contains limited data on the molecular features of signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 84%
“…[1][2][3][4][5][6][7][8][9][10] By definition, 450% of tumor cells have signet ring cell morphology. 11 Signet ring histology is considered an independent adverse prognostic factor by the American Joint Committee on Cancer and the College of American Pathologists.…”
mentioning
confidence: 99%
“…The prognostic significance of mucinous carcinoma is controversial. In some studies, mucinous histology has been shown to be an independent negative prognostic factor (Connelly et al, 1991;Green et al, 1993;Secco et al, 1994), but not in others (Minsky et al, 1987;Green et al, 1993;Enriquez et al, 1998;Consorti et al, 2000). Both the American Joint Committee on Cancer and the College of American Pathologists consider that the mucinous subtype has not been proven as a statistically significant prognostic factor independent of histological grade (Compton et al, 2000a(Compton et al, , 2000b.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Mucinous carcinoma is a histologic subtype constituting 11-15% of colorectal cancer. [17][18][19][20][21] Mucinous histology has been shown to be an independent adverse prognostic factor in some studies, 19,[21][22][23] but not in others. 17,18,20,24,25 The current consensus of the College of American Pathologists (CAP) and American Joint Committee on Cancer is that mucinous differentiation is not proven as a statistically significant prognostic factor independent of histologic grade.…”
mentioning
confidence: 99%